A leucine-rich repeat receptor-like kinase, OsSTLK, modulates salt tolerance in rice. (July 2020) - Lin, Faming; Li, Shen; Wang, Ke; Tian, Haoran; Gao, Junfeng; Zhao, Quanzhi; Du, Changqing
Highlights: OsSTLK is a novel LRR-RLK gene and responds to salt stress in a time and dosage-dependent fashion in rice. OsSTLK overexpression confers high salt tolerance in rice via regulating ROS scavenging system and stomatal patterning. Moreover, Os STLK alters Na + /K + ratio in rice and perhaps involved in MAPK signal pathway. Abstract: Leucine-rich repeat receptor-like kinases (LRR-RLKs) have been widely associated with plant abiotic stress responses. However, the functions of the majority of LRR-RLKs has not been well defined. Here, we identified a novel rice LRR-RLK member involved in salt tolerance and designated as Os STLK ( Oryza sativa L. Salt-Tolerance LRR-RLK). Transcript analysis showed that OsSTLK was significantly induced in response to salt stress in rice shoot and root in a time and dosage-dependent fashion. Phenotypic observations indicated that OsSTLK overexpression exhibited reduced salt sensitivity, and improved salt stress tolerance. Further physiological analysis showed that OsSTLK overexpression remarkably reduced electrolyte leakage, malondialdehyde (MDA) content, reactive oxygen species (ROS) accumulation under salt stress conditions by up-regulating ROS-scavenging activities and modifying stomatal patterning. Moreover, Na + /K + ratio and MAPK phosphorylation level were also reduced in OsSTLK -overexpression transgenic rice plants compared with WT control. Taken together, our findings suggested that Os STLK as an important positive regulator of salt stress tolerance perhaps through regulating ROS scavenging system, Na + /K + ratio and MAPK signal pathway.